A case of an atypical teratoid/rhabdoid tumor with distinctive histology in the pineal region in an adult patient. Issue 11 (2nd September 2021) - Doi, Masatomo; Koike, Junki; Yoshida, Yasuyuki; Nakamura, Hisao; Chosokabe, Motohiro; Naruki, Saeko; Tajima, Shinya; Endo, Akira; Matsumori, Takashi; Tanaka, Yuichiro
Abstract: A 31‐year‐old man suffered from headaches and presented at a hospital after the symptom worsened. Obstructive hydrocephalus and a pineal tumor were identified, and he was transferred to our hospital for further investigation and treatment. Cranial computed tomography revealed a hypodense mass lesion on the right of the pineal region, and calcifications and enlargement of the lateral and third cerebral ventricles were also evident. Blood tests were negative for all tumor markers. Laparoscopic biopsy and third‐ventricle fenestration were performed that day as an emergency surgery to treat the obstructive hydrocephalus. Postoperative cranial magnetic resonance imaging revealed a solid tumor that was hypointense on T1‐weighted imaging, hyperintense on T2‐weighted imaging, and heterogeneously enhanced by Gd. Subsequently, the tumor increased in size, and craniotomy and tumorectomy were performed. Histologically, the tumor proliferated as round or short spindle‐shaped cells in a myxoid matrix, forming arrays that surrounded the blood vessels. As a few cells with eosinophilic cytoplasm were also present and immunostaining for INI‐1 was negative, the patient was diagnosed with atypical teratoid/rhabdoid tumor (AT/RT). AT/RT of the pineal region in adults is rare, and herein, we report the morphological characteristics of this case and reviewed the relevant literature.